2005
DOI: 10.1542/peds.2004-1161
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Lead, Mercury, Mirex, Dichlorodiphenyldichloroethylene, Hexachlorobenzene, and Polychlorinated Biphenyls to Timing of Menarche Among Akwesasne Mohawk Girls

Abstract: ABSTRACT. Background. Children are commonly exposed at background levels to several ubiquitous environmental pollutants, such as lead and persistent organic pollutants, that have been linked to neurologic and endocrine effects. These effects have prompted concern about alterations in human reproductive development. Few studies have examined the effects of these toxicants on human sexual maturation at levels commonly found in the general population, and none has been able to examine multiple toxicant exposures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
153
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(159 citation statements)
references
References 44 publications
(55 reference statements)
1
153
1
4
Order By: Relevance
“…However the high blood concentrations of lead and cadmium observed by Schroijen et al (2008) in adolescents from Antwerp and the Antwerp harbour could have contributed to the delay in sexual maturation observed for these adolescents. Indeed, high lead levels in blood were already reported to be associated to a delayed pubertal development in girls (Denham et al, 2005;Selevan et al, 2003Selevan et al, , 2004Wu et al, 2003). Among the female adolescents who participated in our biomonitoring study, Den Hond et al (submitted) observed a significant negative association between blood lead concentration and development of pubic hair (odds ratio for doubling of exposure is 0.65; p ¼ 0.020).…”
Section: Article In Pressmentioning
confidence: 63%
“…However the high blood concentrations of lead and cadmium observed by Schroijen et al (2008) in adolescents from Antwerp and the Antwerp harbour could have contributed to the delay in sexual maturation observed for these adolescents. Indeed, high lead levels in blood were already reported to be associated to a delayed pubertal development in girls (Denham et al, 2005;Selevan et al, 2003Selevan et al, , 2004Wu et al, 2003). Among the female adolescents who participated in our biomonitoring study, Den Hond et al (submitted) observed a significant negative association between blood lead concentration and development of pubic hair (odds ratio for doubling of exposure is 0.65; p ¼ 0.020).…”
Section: Article In Pressmentioning
confidence: 63%
“…In some other studies, similar results were reported. Higher serum concentrations of the potentially estrogenic PCB congeners 52, 70, 101 [ þ 90] and 187 were associated with a significantly greater probability of having reached menarche (Denham et al, 2005), whereas in Yucheng boys accidentally exposed to high levels of PCBs and polychlorinated dibenzofurans, shorter penile length suggesting pubertal delay was reported (Guo et al, 2004). Delayed initiation of breast development was found in girls with higher prenatal dioxin exposure .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent cross-sectional study of Akwesasne Mohawk Girls, a high concentration of blood PCB indicated a higher probability of having reached menarche, i.e. that highly exposed females tended to be younger at menarche (Denham et al 2005). Contradictory to this study, Vasiliu et al (Vasiliu et al 2004) found that in utero exposure to DDE, but not PCB, resulted in reduced age at menopause.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on women with high consumption of fish from the Baltic Sea or from the Great Lakes have suggested that high dietary exposure to POPs may cause damage to the female reproductive system, measured as time to pregnancy and delayed conception (Buck et al 2000, McGuinness et al 2001, as well as menstrual cycle length (Axmon et al 2004, Mendola et al 1997. Furthermore, increasing blood levels of PCB may be associated with decreasing age at menarche (Denham et al 2005). Animal studies have found that in utero exposure to the PCB congener 2,2'4,4',5,5'-hexachlorobiphenyl (CB-153), but not the congener 3, 3',4,4',, tend to delay onset of puberty in female goats (Lyche et al 2004).…”
Section: Introductionmentioning
confidence: 99%